Neglected lead tip erosion: An unusual case of S‐ICD inappropriate shock. (25th September 2020) - Mitacchione, Gianfranco; Schiavone, Marco; Gasperetti, Alessio; Viecca, Maurizio; Curnis, Antonio; Forleo, Giovanni B.
Abstract: A 52‐year‐old man experienced a subcutaneous implantable cardioverter‐defibrillator (S‐ICD) inappropriate shock due to electrode tip decubitus. The device, implanted two years before with a three‐incision technique, was extracted, and a new electrode was implanted along the contralateral parasternal line with a two‐incision technique, in a one‐stage procedure. One‐year follow‐up was eventless. Early S‐ICD electrode extraction and reimplantation during the same procedure is effective and should be considered as soon as initial signs of decubitus appear to avoid inappropriate shocks. A two‐incision technique should be preferred to reduce the risk of electrode tip decubitus.